Effect of noble metal species and compositions on manganese dioxide-modified carbon nanotubes for enhancement of alcohol oxidation - C. Panrod (2018)
© 2018 Hydrogen Energy Publications LLC By integrating the effects of alloying, chemical composition and support, a series of mono- and bi-metallic catalyst nanoparticles electrodeposited on α-manganese dioxide (MnO2)-modified carbon nanotube (CNT) supports were synthesized to improve the efficiency of direct alcohol fuel cells. Small and dispersed nanoparticles on the CNT/MnO2surfaces with high electrochemically active surface area (ECSA) were successfully obtained in this work. The support materials were characterized by Fourier-transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD), while the as-prepared catalysts were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). Cyclic voltammetry (CV) and chronoamperometry (CA) were used to study the activity and stability of the catalysts, respectively. The results showed that a combination of Pt, Pd, Au and MnO2on the CNTs significantly affected the topography of the composite catalyst surfaces, and their electrochemical measurements showed excellent electrocatalytic activity toward the reaction. For methanol and ethanol oxidation in acid solution, CNT/MnO2/1M3Pt (M = Pd or Au) catalysts revealed greater activity improvement compared to the other prepared catalysts. For the bimetallic CNT/MnO2/xMyPt catalysts, the values of the forward peak current (If)) and the ratio of the forward peak current to the reverse peak current (If/Ib) were higher, while their onset potentials (Eo) were lower compared to those of the monometallic CNT/MnO2/4Pt catalyst. Moreover, CO oxidation on these bimetallic catalysts was also confirmed to be poisoning resistant. These results indicate that our prepared catalyst showed excellent electrocatalytic performance, reliability, and stability. The catalytic activity improvement was based upon the unique integrated structural and functional properties and the synergistic effect of different compositions in the catalyst system.